HYPOGLYCEMIC, HYPOLIPIDEMIC AND ANTIOXIDANT POTENTIALS OF SPECIALLY FORMULATE POLYHERBAL, FORMULATION IN STREPTOZOTOCIN INDUCED DIABETIC RATS - Mishra, Jhansee; Dash, Alok Kumar; Dash, Deepak Kumar (European Scientific Journal, ESJ, 2014)
Objective: To investigate the antihyperglycemic, hypolipidemic and antioxidant properties of the specially formulate polyherbal formulation in Streptozotocin induced diabetic rats. Methods: Multifactorial metabolic diseases, for instance diabetes develop several complications like hyperlipidemia, hepatic toxicity, immunodeficiency etc., Hence, instead of mono-drug therapy the management of the disease requires the combination of herbs. Marketed herbal drugs comprise of irrational combinations which makes their quality control more difficult. Phytoconstituents, despite having excellent bioactivity in vitro demonstrate less or no in vivo actions due to their poor lipid solubility, resulting in high therapeutic dose regimen. In the present study, polyherbal formulation of aqueous extracts of Azadirachta indica, Camellia sinensis and ethanol extract Asparagus racemosus F1 (N:G:S=2:2:1) 200 mg/kg2:2:1, named F1, optimized based on STZ induced diabetic rats found to be significant decrease (P<0.01) in blood glucose level as compared to the diabetic control group of animals. Results: Diabetes was induced in Albino rats by administration of streptozotocin (45mg/kg, I.P). The F1 (N:G:S=2:2:1) 200 mg/kg body weight was administered to diabetes induced rats for a period of 28 days, which possess better effect than F2 (N:G:S=2:1:2) 200 mg/kg and F3 (N:G:S=2:1:1) 200 mg/kg. Other biochemical parameters such as serum cholesterol, triglycerides, HDL-cholesterol, VLDL-cholesterol, LDLcholesterol, urea, creatinin and proteins levels were also measured at the end of study. After checking the antidiabetic activity the F1 (N:G:S=2:2:1) 200 mg/kg on blood glucose was observed the best one, in order to justify it oxidative parameter , i.e.- superoxide dismutase (SOD), reduced glutathione (GSH) , serum thiobarbituric (TBAR) and LPO were also tested. These enzymes indicates its oxidative stress. Conclusion:From the above results it is concluded that the formulation F1 (N:G:S=2:2:1) 200 mg/kg on blood glucose possesses significant antidiabetic,hypolipidemic and antioxidant effects in streptozotocin induced diabetic rats .